2011
DOI: 10.1002/jnr.22713
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of full‐length BK channel variants in the developing mouse cochlea

Abstract: Maxi K+ (BK) channel diversity is attributed to alternative splicing in the kcnma1 gene. The resultant variants manifest themselves in different cell types, tissues and functions such as excitation, metabolism, and signaling. Immuno-electron microscopy revealed immunogold particle labeling of BK in apical and basal regions of inner and outer hair cells, respectively. Additional labeling occurs in Deiters’ cells and the inner mitochondrial membrane. Identification of full-length sequences reveals 27 BK variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
0
34
1
Order By: Relevance
“…As shown in Fig 6a, a sequence of 26-28 homologous amino acids that can be identified as exon 29 is present in the chick cochlea [22] and the skate electroreceptor. A virtually identical sequence was identified as alternative exon B in an early description of the mouse B K channel [7] and later in the mouse cochlea [38] and the rat [17,35]. Fluorescence imaging studies have shown that exon 29 occurs in inner hair cells of the mouse cochlea, which are the primary auditory receptor cells [5].…”
Section: 1 Resultsmentioning
confidence: 99%
“…As shown in Fig 6a, a sequence of 26-28 homologous amino acids that can be identified as exon 29 is present in the chick cochlea [22] and the skate electroreceptor. A virtually identical sequence was identified as alternative exon B in an early description of the mouse B K channel [7] and later in the mouse cochlea [38] and the rat [17,35]. Fluorescence imaging studies have shown that exon 29 occurs in inner hair cells of the mouse cochlea, which are the primary auditory receptor cells [5].…”
Section: 1 Resultsmentioning
confidence: 99%
“…A short REVIEWS PHYSIOLOGY • Volume 28 • March 2013 • www.physiologyonline.org stretch of ϳ20 residues connects the transmembrane helix S6 and RCK1 (S6-RCK1 linker), whereas ϳ100 or more residues bridge RCK1 and RCK2 (RCK1-RCK2 linker). Several splice variants that differ in the S6-RCK1 linker, the RCK1-RCK2 linker, and/or the distal COOH-terminal areas are known (125).…”
Section: Snapshots Of the Bk Channel Structurementioning
confidence: 99%
“…For example, although only one gene codes for the pore-forming subunit (KCNMA1, Slo1), its transcript is extensively spliced to create a vastly large number of variant polypeptides (1,36,40,141). Nearly 1,000 distinct full-length polypeptides may be theoretically available to form tetrameric BK channels in mice (125). Coassembly with the auxiliary subunits ␤1, ␤2, ␤3, ␤4, and leucine-rich repeat-containing proteins (LRRCs; ␥ subunits) also increases functional diversity by altering the channel's apparent sensitivity to Ca 2ϩ and V m as well as their kinetic properties including activation, deactivation, and in some cases conferring inactivation (11,17,156,161,165,170,176,177).…”
mentioning
confidence: 99%
“…NMDA2B receptors are present in spiral ganglion cells and adjacent to inner and outer hair cells of human cochlea [39]. Similarly, BK channels are found in ganglion cells and at the base of outer hair cells [19].…”
Section: Discussionmentioning
confidence: 98%
“…Both BK mito and K ATP channels are thought to protect against ischemia by inhibiting the PTP, either by direct physical interaction or by inhibiting the factors that initiate the opening of the PTP [40]. Recent evidence suggests the presence of BK mito in the cochlea [9], [19], although its relation to ATP synthase and the PTP requires further studies.…”
Section: Discussionmentioning
confidence: 99%